Impact of thermal pretreatment and MSW origin on composition and hydrolysability in a sugar platform biorefinery. (March 2018) - Vaurs, L P; Heaven, S; Banks, C J
Abstract: Municipal solid waste (MSW) is a widely available large volume source of lignocellulosic material containing a waste paper/cardboard mixture which can be converted into fermentable sugars via cellulolytic enzyme hydrolysis in a sugar platform biorefinery. Thermal pretreatments are generally applied to MSW to facilitate the extraction of the lignocellulosic material from recyclable materials (plastics, metals etc.) and improve the paper pulp conversion to sugars. Applying high temperature might enhance food waste solubilisation but may collapse cellulose fibre decreasing its hydrolysability. Low temperature pre-treatment will reduce the energy demand but might result in highly contaminated pulp. Preliminary results showed that the enzymatic hydrolysis performances were dependent on the MSW origins. Using 8 different samples, the impact of thermal pretreatment and MSW origin on pulp composition and hydrolysability was assessed in this work. Low pre-treatment temperature produced pulp which contained less lignocellulosic material but which hydrolysed to a higher degree than MSW treated at high temperatures. High temperature pre-treatment could have exposed more of the inhibiting lignin to cellulase. This information would have a significant economic impact on a commercial plant as expensive autoclave could be advantageously replaced by a cheaper process. Glucan conversions were also found to vary depending on the region, the recycling rate possibly because of the lower recycling rate resulting in the use of less paper additive in the material or the difference in paper production technology (chemical VS mechanical pulping). This could also be explained by the differences in paper composition.